2012
DOI: 10.12688/f1000research.1-33.v1
|View full text |Cite
|
Sign up to set email alerts
|

CA72-4 may contribute to real-time reconnaissance of gastric cancer

Abstract: Objective: Data from prospective studies indicate a positive impact of gastric cancer screening programs on mortality associated with the disease. Unfortunately, endoscopic procedures, widely regarded as uncomfortable, face low patient compliance, thus underscoring the need for reliable biological markers capable of detection of tumor growth in bodily fluids. Furthermore, in light of the emerging patient-friendly, still devoid of histopathological capabilities, capsule endoscopy, gastric fluid may prove valuab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the last decade, 45% of published studies that explored the role of non‐blood‐based circulating biomarkers in GC detection characterized GJ samples following a case‐control study design and mostly including Han Chinese participants (23 of 36 reports) 67–89 . A high level of heterogeneity regarding the class of analyzed biomarkers was observed: (a) 17 studies focused on distinct nucleic acids, including mRNA, miRNA, long non‐coding RNA (lncRNA), long intergenic non‐coding RNA (lincRNA), piwi‐interacting RNA (piRNA), circular RNA, and DNA 67,68,71,74–79,81–86,88,90 ; (b) nine studies on proteins or amino acids 69,70,72,80,91–94 ; (c) four studies primarily on metabolites 95–98 ; (d) two studies focused on glycoproteins, including CEA, CA19‐9, CA72‐4, and CA50 99,100 ; (e) two studies on microbiota 89,101 ; (f) one study on intrinsic fluorescence spectra 87 ; (g) one study on blood 102 . GC‐associated biomarkers found in GJ with reported expression, AUC, or sensitivity and specificity values, are summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, 45% of published studies that explored the role of non‐blood‐based circulating biomarkers in GC detection characterized GJ samples following a case‐control study design and mostly including Han Chinese participants (23 of 36 reports) 67–89 . A high level of heterogeneity regarding the class of analyzed biomarkers was observed: (a) 17 studies focused on distinct nucleic acids, including mRNA, miRNA, long non‐coding RNA (lncRNA), long intergenic non‐coding RNA (lincRNA), piwi‐interacting RNA (piRNA), circular RNA, and DNA 67,68,71,74–79,81–86,88,90 ; (b) nine studies on proteins or amino acids 69,70,72,80,91–94 ; (c) four studies primarily on metabolites 95–98 ; (d) two studies focused on glycoproteins, including CEA, CA19‐9, CA72‐4, and CA50 99,100 ; (e) two studies on microbiota 89,101 ; (f) one study on intrinsic fluorescence spectra 87 ; (g) one study on blood 102 . GC‐associated biomarkers found in GJ with reported expression, AUC, or sensitivity and specificity values, are summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…a Only microbiota genera and species with reported relative abundance and reaching AUC >0.70 were included (suggested by 38 as moderate accuracy). b P < 0.001. c Klebsiella, Subdoligranulum, Prevotella 9, Streptococcus, Ruminiclostridium 9.LOPES ET AL.T A B L E 3 CA5099,100 ; (e) two studies on microbiota89,101 ; (f) one study on intrinsic fluorescence spectra87 ; (g) one study on blood 102. GCassociated biomarkers found in GJ with reported expression, AUC, or sensitivity and specificity values, are summarized in Table4.…”
mentioning
confidence: 99%
“…However, this level is increased by various diseases such as gastrointestinal disorders, gastric ulcers, and intestinal epithelium. It has been reported that when setting 100 U/ml as the risk level, the sensitivity is increased to 79% and the specificity is increased to 89% [27].…”
Section: Discussionmentioning
confidence: 99%